(untitled) (Research, Society and Development, 2021)
The objective is to investigate the main origins by Badminton athletes, how they manifest themselves and the impact on the athlete’s performance. This is an observational, quantitative research, carried out in a sports club, from September to October 2020, after approval by the Ethics Committee of the UNIFACID University Center, under the number of opinions 4,276,525. Badminton athletes were included, with at least 1 year of practice in the sport. The data were collected through the electronic questionnaire (Google Forms). The data were analyzed using SPSS 20.0, followed by the Kolmogorov-Smirnov test, p<0.05 was considered significant. 31 athletes participated, 51.6% (n=16) female and 48.4% (n=15) male, with a mean age of 17.9 years (± 2.6). All (100%, n=31) with a competitive profile, making an average of 8.4 years (± 2.7) of time in sport and 5.8 days (± 0.9) of training pace per week. 41.9% had pain, discomfort or injury, with predominant involvement in the knee (38.7%, n=12) and shoulder (12.9%, n=4). 75.0% of the injuries were classified as mild and 100% with severe injury (p=0.011), however, without association of pain, discomfort or injury with gender (p=0.722), due to the injury (p=0.275), instability articular (p=0.059) and interference of lesions in daily activities (p=0.262). The athletes are veterans within the sport and have an intense sequence of training per week, however, as it is a high intensity sport, it overloads the knee and shoulder joints, culminating in joint instability and a drop in sports performance.